2010
DOI: 10.1007/s12253-010-9263-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Alpha Polymorphisms and the Risk of Malignancies

Abstract: Estrogens represent risk factors for endocrinerelated cancers and play also an important role in the development and progression of other malignancies. In order to analyze the associations between estrogen receptor gene alpha polymorphisms and cancers susceptibility, we genotyped six single nucleotide polymorphisms (SNPs) in 163 Caucasian cancer patients-103 breast cancers and 60 other malignancies (colorectal, bladder, hepatocellular carcinoma and acute myeloid leukemia)-and 114 healthy controls using hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…However, the results remained to be inconsistent for different cancers. Moreover, the results were [17,[24][25][26]. Therefore, we performed this meta-analysis to estimate the associations between ESR1 polymorphisms and cancer risk for achieving more comprehensive and accurate conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results remained to be inconsistent for different cancers. Moreover, the results were [17,[24][25][26]. Therefore, we performed this meta-analysis to estimate the associations between ESR1 polymorphisms and cancer risk for achieving more comprehensive and accurate conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…1. For rs1801132 (C > G), only 22 studies with available data were enrolled in the pooled analysis, which two papers with three cancer types presented three separate studies individually [17,18]. Breast cancer (nine studies), colorectal cancer (two studies), gallbladder cancer (two studies), prostate cancer (three studies), HCC (two studies) and the others were included in the pooled analysis.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…The rs3798577 C allele was previously associated with cancer risk, 47 lower circulating estradiol concentrations in African American women 48 and lower bone mineral density in Japanese women. 49 Sowers et al 50 reported that Japanese women carrying the rs3798577 C/T allele displayed lower apoA-I and HDL-C levels.…”
Section: Discussionmentioning
confidence: 90%
“…There are several studies about association between rs3798577 and breast cancer. Anghel et al (2010) found strong association of variant C allele of rs3798577 polymorphism with the risk of breast cancer (p = 0.0007). On the other hand, Li et al (2010) in meta-analysis did not find any association of rs3798577 polymorphism with breast cancer risk.…”
Section: Discussionmentioning
confidence: 95%
“…The second studied polymorphism, rs3798577, is located in 3′-UTR of ER-α gene. Although its functionality is not yet known, taken in account that 3′-UTR region is associated with the preferred target for microRNAs and splicing factors, it seems to modulate the ER-α expression (Anghel et al 2010). Exact impact of both our selected polymorphisms is still unknown, but there is evidence that also silent mutations could cause a structural change in RNA, altering translation efficacy, and thereby leading to change in gene expression rate.…”
Section: Introductionmentioning
confidence: 99%